2014
DOI: 10.1007/s12010-014-1217-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Susceptibility to Mycobacterium tuberculosis: a Close View of Immunological Defence Mechanism

Abstract: Tuberculosis is the most deadly infectious disease. In particular, pulmonary tuberculosis, being the predominant one, is highly contagious. In past the 200 years, one billion tuberculosis (TB) deaths had occurred, and it is anticipated that in the next 25 years, more than 40 million people may be killed by TB unless control measures are implemented. There are various causes which increase the susceptibility to Mycobacterium tuberculosis infection; these include weakened immune system which occurs through vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…This is not unexpected as earlier studies have found alcohol abuse to be associated with non-adherence to TB treatment and unsuccessful TB treatment outcome [4,[29][30][31]. In addition, alcohol abuse has been linked to a compromised immune system and consequently a higher risk of developing more severe forms of TB [32]. All these factors can potentially contribute to a higher risk of mortality in patients suffering from alcohol abuse.…”
Section: Plos Onementioning
confidence: 73%
“…This is not unexpected as earlier studies have found alcohol abuse to be associated with non-adherence to TB treatment and unsuccessful TB treatment outcome [4,[29][30][31]. In addition, alcohol abuse has been linked to a compromised immune system and consequently a higher risk of developing more severe forms of TB [32]. All these factors can potentially contribute to a higher risk of mortality in patients suffering from alcohol abuse.…”
Section: Plos Onementioning
confidence: 73%
“…E.g., most people with tuberculosis were tobacco smokers (64%) or heavy alcohol users (35%) in our study and we observed elevated all-term SIRs for smoking- or alcohol-related cancers, thus it is plausible that tobacco smoking and alcohol intake are important shared risk factors. Finally, malnutrition is a risk factor for tuberculosis and low body mass index (BMI) is prevalent in tuberculosis patients [32, 33]. There is substantial evidence that obesity increases the risks of breast, endometrial, ovarian cancer, malignant melanoma as well as some other cancers; its influence is most likely mediated through hormonal mechanisms [20].…”
Section: Discussionmentioning
confidence: 99%
“…Further it was seen that this diminished level of cytokines is associated with proinflammatory cytokines such as IL-1 β and IL-18 which were also found to be diminished; however no links were found with the diminished level of type 2 cytokines. Moreover, patient suffering from DM was found to have inhibited level of MTB antigen specific cytokines (type 1 and type 17) [41]. Elevation in resistin level, a protein produced by immune cells in humans, diminishes the activation of mycobacterium-induced inflammasome through suppressing ROS production in leukocytes [42].…”
Section: Dm Enhances Susceptibility To Tb Infectionmentioning
confidence: 99%